HARGA SAHAM PT ELANG MAHKOTA TEKLONOLOGI TBK DIPENGARUHI OLEH RASIO LANCAR, MARGIN LABA KOTOR DAN RASIO UTANG TERHADAP EKUITAS - Arief Rachmawan Assegaf (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to analyze the effect of current ratio, gross profit margin and debt to equity ratio on the share price of PT Elang Mahkota Teknologi Tbk. Data were analyzed using multiple linear regression analysis secondary data sourced from the financial statements of PT Elang Mahkota Teknologi Tbk for the period 2011- 2019. The results of t-test research show that current ratio has a significant positive effect on stock prices, while the gross profit margin and debt to equity ratio variables have a significant negative effect on stock prices. The results of the F test show that the current rasio, gross profit margin and debt to equity ratio simultaneously have a significant effect on stock prices.